The Matter, Chemical Reaction and Thermodynamic Models as Structuring Cores of a Citizenship- Oriented School Chemistry [Los Modelos Materia, Reacción Química y Termodinámica Como Núcleos Estructurantes de Una Química Escolar Orientada a la Formación Ciudadana] - Manrique-Rodriguez, F (Facultad de Quimica, UNAM, 2021)
The present work proposes to consider models as structuring nuclei of school Chemistry school with the aim of overcoming the current curricular challenges and orienting chemistry education towards citizenship education. Through the analysis of the existing literature in the field of the curricular organization of School Chemistry, the matter, chemical reaction and thermodynamic models are identified and characterized as the nuclei of School Chemistry by identifying the conditions, entities, properties, activities and organization that student representations about material systems are expected to include, to reason about a set of relevant facts for citizen education. © 2021 Facultad de Quimica, UNAM. All rights reserved.